Alkaline phosphatase expression during relapse after orthodontic tooth movement - Pinandi Sri Pudyani; Widya Asmara; Ika Dewi Ana; Tita Ratya Utari (Dental Journal (Majalah Kedokteran Gigi), 2014)
Background: The increasing of osteoblast activities during bone formation will be accompanied with the increasing expression of alkaline phosphatase enzyme (ALP). ALP can be obtained from clear fluid excreted by gingival crevicular fluid (GCF). Bone turnover, especially bone formation process, can be monitored through the expression of ALP secreted by GCF during orthodontic treatment. Thus, retention period is an important period that can be monitored through the level of bone metabolism around teeth. Purpose: This research were aimed to determine the relation of distance change caused by tooth relapse and ALP activities in gingival crevicular fluid after orthodontic; and to determine ALP as a potential biomarker of bone formation during retention period. Methods: Lower incisors of 25 guinea pigs were moved 3 mm to the distally by using open coil spring. Those relapse distance were measured and the gingival crevicular fluid was taken by using paper points to evaluate ALP levels on days 0, 3, 7, 14 and 21 respectivelly by using a spectrophotometer (405 nm). t-test and ANOVA test were conducted to determine the difference of ALP activities among the time intervals. The correlation regression analysis was conducted to determine the relation of distance change caused by the relapse tooth movement and ALP activities. Results: The greatest relapse movement was occurred on day 3 after open coil spring was removed. There was significant difference of the average of distance decrease among groups A1-A5 (p<0.05). It was also known that ALP level was increased on day 3, but there was no significant difference of the average level of ALP among groups A1-A5 (p>0.05). Finally, based on the results of correlation analysis between the ALP level decreasing and the relapse distance on both right and left of mesial and distal sides, it is known that there was no relation between those two variables (p>0.05). Conclusion: It can be concluded that relapse after orthodontic tooth movement occurs rapidly as the teeth are free from orthodontic force. ALP level can be detected through gingival crevicular fluid during relapse by using a spectrophotometer.Latar belakang: Peningkatan aktivitas osteoblas selama pembentukan tulang akan disertai peningkatan ekspresi enzim alkalin fosfatase (Alkaline Phosphatase/ALP). Sumber ALP dapat diperoleh dari cairan bening yang diekskresi celah gingiva gigi yang dikenal sebagai cairan krevikuler gingiva (gingival crevicular fluid/GCF). Bone turnover terutama proses pembentukan tulang dapat dimonitor melalui ekspresi ALP cairan krevikuler gingiva selama perawatan ortodonti. Periode retensi merupakan periode yang penting. Kesulitan memecahkan masalah retensi akan dapat ditangani dengan memonitor tingkat metabolisme tulang disekitar gigi. Tujuan: Penelitian ini bertujuan untuk meneliti perubahan jarak relapse gigi dan aktivitas ALP pada cairan krevikuler gingiva setelah digerakkan secara ortodonti dan potensi ALP sebagai biomarker pembentukan tulang pada periode retensi. Metode: Gigi insisivus bawah 25 ekor marmot digerakkan ke distal menggunakan opencoil spring sampai mencapai jarak ± 3 mm, diukur gerakan relapse gigi dan pengambilan cairan krevikuler gingiva menggunakan paper point untuk dievaluasi kadar ALP pada hari ke 0, 3, 7, 14 dan 21 menggunakan spektrofotometer (405 nm). Analisis t-test dan anova untuk mengetahui perbedaan aktivitas ALP antar interval waktu dan analisis regresi korelasi untuk mengetahui hubungan besarnya jarak relapse dengan aktivitas ALP. Hasil: Pergerakan relapse yang paling besar terjadi pada hari ke 3 setelah opencoil spring dilepas. Terdapat perbedaan rata-rata penurunan jarak antar kelompok A1-A5 yang signifikan (p<0,05). Kadar ALP mengalami peningkatan pada hari ke 3, namun tidak terdapat perbedaan rata-rata yang signifikan kadar ALP antar kelompok A1-A5 (p>0,05). Hasil uji korelasi antara penurunan jarak dengan kadar ALP pada mesial distal gigi baik kanan maupun kiri tidak menunjukkan adanya hubungan kedua variabel (p>0,05). Simpulan: Relapse pada perawatan ortodonti terjadi secara cepat ketika gigi terbebas dari gaya ortodonti. Kadar ALP dapat terdeteksi dari cairan krevikuler gingiva pada pergerakan relapse gigi menggunakan spektrofotometer.